HepaChip-MP – a twenty-four chamber microplate for a continuously perfused liver coculture model. Issue 16 (14th July 2020) - Busche, Marius; Tomilova, Olena; Schütte, Julia; Werner, Simon; Beer, Meike; Groll, Nicola; Hagmeyer, Britta; Pawlak, Michael; Jones, Peter D.; Schmees, Christian; Becker, Holger; Schnabel, Juliane; et al.
Abstract : HepaChip-MP: a 24-culture-chamber, automated microfluidic in vitro model of the liver sinusoid in multiwellplate format. Abstract : HepaChip microplate (HepaChip-MP) is a microfluidic platform comprised of 24 independent culture chambers with continuous, unidirectional perfusion. In the HepaChip-MP, an automated dielectrophoresis process selectively assembles viable cells into elongated micro tissues. Freshly isolated primary human hepatocytes (PHH) and primary human liver endothelial cells (HuLEC) were successfully assembled as cocultures aiming to mimic the liver sinusoid. Minimal quantities of primary human cells are required to establish micro tissues in the HepaChip-MP. Metabolic function including induction of CYP enzymes in PHH was successfully measured demonstrating a high degree of metabolic activity of cells in HepaChip-MP cultures and sufficient sensitivity of LC-MS analysis even for the relatively small number of cells per chamber. Further, parallelization realized in HepaChip-MP enabled the acquisition of dose–response toxicity data of diclofenac with a single device. Several unique technical features should enable a widespread application of this in vitro model. We have demonstrated fully automated preparation of cell cultures in HepaChip-MP using a pipetting robot. The tubeless unidirectional perfusion system based on gravity-driven flow can be operated within a standard incubator system. Overall, the system readily integrates in workflows common in cell culture labs. Further research will be directed towards optimization of media composition to further extend culture lifetime and study oxygen gradients and their effect on zonation within the sinusoid-like microorgans. In summary, we have established a novel parallelized and scalable microfluidic in vitro liver model showing hepatocyte function and anticipate future in-depth studies of liver biology and applications in pre-clinical drug development.